Critical impact of radiotherapy protocol compliance and quality in the treatment of retroperitoneal sarcomas: Results from the EORTC 62092‐22092 STRASS trial. Issue 14 (10th May 2022) - Haas, Rick; Stelmes, Jean‐Jacques; Zaffaroni, Facundo; Sauvé, Nicolas; Clementel, Enrico; Bar‐Deroma, Raquel; Le Péchoux, Cécile; Litière, Saskia; Marreaud, Sandrine; Alyamani, Najlaa; Andratschke, Nicolaus H. J.; Sangalli, Claudia; et al.
Abstract : Background: The European Organization for Research and Treatment of Cancer 22092‐62092 STRASS trial failed to demonstrate the superiority of neoadjuvant radiotherapy (RT) over surgery alone in patients with retroperitoneal sarcoma. Therefore, an RT quality‐assurance program was added to the study protocol to detect and correct RT deviations. The authors report results from the trial RT quality‐assurance program and its potential effect on patient outcomes. Methods: To evaluate the effect of RT compliance on survival outcomes, a composite end point was created. It combined the information related to planning target volume coverage, target delineation, total dose received, and overall treatment time into 2 groups: non–RT‐compliant (NRC) for patients who had unacceptable deviation(s) in any of the previous categories and RT‐compliant (RC) otherwise. Abdominal recurrence‐free survival (ARFS) and overall survival were compared between the 2 groups using a Cox proportional hazard model adjusted for known prognostic factors. Results: Thirty‐six of 125 patients (28.8%) were classified as NRC, and the remaining 89 patients (71.2%) were classified as RC. The 3‐year ARFS rate was 66.8% (95% confidence interval [CI], 55.8%‐75.7%) and 49.8% (95% CI, 32.7%‐64.8%) for the RC and NRC groups, respectively (adjusted hazard ratio, 2.32; 95% CI, 1.25‐4.32; P = .008). Local recurrence after macroscopic complete resection occurred in 13 of 89 patients (14.6%) versus 2 of 36 patients (5.6%) in the RC and NRC groups, respectively. Conclusions: The current analysis suggests a significant benefit in terms of ARFS in favor of the RC group. This association did not translate into less local relapses after complete resection in the RC group. Multidisciplinary collaboration and review of cases are critical to avoid geographic misses, especially for rare tumors like retroperitoneal sarcoma. Abstract : This analysis suggested a significant benefit in terms of abdominal recurrence‐free survival in favor of the radiotherapy‐compliant group but not in terms of local relapse. Multidisciplinary collaboration and review of cases were critical to avoid geographic misses, especially for rare tumors like retroperitoneal sarcoma.